MODE, MEANING, AND SYNAESTHESIA IN MULTIMEDIA L2 WRITING - Mark Evan Nelson (Language Learning and Technology)
This study of digital storytelling attempts to apply Kress's (2003) notions of synaesthesia, transformation, and transduction to the analysis of four undergraduate L2 writers' multimedia text creation processes. The students, entering freshmen, participated in an experimental course entitled "Multimedia Writing," whose purpose was to experience and explore the processes of multimodal textual communication. With the support of empirical data drawn from interviews, student journals, and the digital story-related artifacts themselves, the author shows how synaesthetically derived meaning may be a natural part of the process of creating multimodal texts. Considering the special case of non-native English speakers, the paper also demonstrates that synaesthesia may have both amplifying and limiting effects on the projection of authorial intention and voice. Before reading the following, it is suggested that the reader view examples of the multimedia essays discussed herein.